+0  
 
0
214
2
avatar

Define the operation \(\star\) by \(a \star b = (a + b)b \). What is \((3\star5) - (5\star3)\)?

 Apr 13, 2019
 #1
avatar+111431 
+2

a*b   = (a + b)b  =  ab + b^2

 

So

 

(3 * 5) - (5 * 3)  =

 

[3*5 + 5^2]  - [ 5*3 + 3^2]  =

 

[ 15 + 25 ] - [ 24 ]  =

 

40 - 24  =

 

16

 

Thanks to guest for catching my errors    !!!!

 

cool cool cool

 Apr 14, 2019
edited by CPhill  Apr 14, 2019
 #2
avatar
0

CPhill: Did you make a mistake in the 2nd line?

 

(3 * 5) - (5 * 3)  =

 

[3*5 + 5^2]  - [ 5*3 - 3^2]  =Souldn't this read: [3*5 + 5^2] - [5*3 + 3^2]

 

[ 15 + 25 ] - [ 15 - 9 ]  = [15 + 25] - [15 + 9] =40 - 24 = 16 ???

 Apr 14, 2019

29 Online Users

avatar
avatar
avatar
avatar
avatar